SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-0587
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Modeling Driver Reach

Abstract: The reach capability of drivers is currently represented in vehicle design practice in two ways. The SAE Recommended Practice J287 presents maximum reach capability surfaces for selected percentiles of a generic driving population. Driver reach is also simulated using digital human figure models. In typical applications, a family of figure models that span a large range of the target driver population with respect to body dimensions is positioned within a digital mockup of the driver's workstation. The articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…What they found was that the soft tissue around the greater trochanterion of the hip appears to provide the maximum excursion limit for the center of pressure during lateral reaches. This is a much larger excursion than normally assumed in Figure 3 Illustrations of the complex pelvic orientations and spinal column curvatures associated with four different arm-reaching tasks in a seated posture (from Reed et al, 2003).…”
Section: Seated Balance During Reaching Motionsmentioning
confidence: 98%
See 1 more Smart Citation
“…What they found was that the soft tissue around the greater trochanterion of the hip appears to provide the maximum excursion limit for the center of pressure during lateral reaches. This is a much larger excursion than normally assumed in Figure 3 Illustrations of the complex pelvic orientations and spinal column curvatures associated with four different arm-reaching tasks in a seated posture (from Reed et al, 2003).…”
Section: Seated Balance During Reaching Motionsmentioning
confidence: 98%
“…The torso often is geometrically modeled with a large number of links, sometimes mimicking the vertebral column, but the underlying kinematics model that predicts the relative motions of these segments is a highly reduced model, often using simple proportionality rules for each segment's movements relative to the motion of the entire column. Reed, Parkinson, and Chaffin (2003) discuss this issue and propose a much more sophisticated model, one that is based on careful observations of the curvature changes in the spinal column and rotations of the pelvis of people reaching around a seated workplace. Some results of this study are illustrated in Figure 3. …”
Section: Spinal-pelvic Motion Modelingmentioning
confidence: 99%
“…accommodation percentiles, and do not provide any guidance on the difficulty of reaches that are attainable. Reed et al (2003) demonstrated the experiment approach to obtain human reach envelopes. It entails three steps:…”
Section: Methods For Human Reach Envelopesmentioning
confidence: 99%
“…The first method involves experimental-based methods using a large number of subjects to visualize human reach (Badler, 1997;Chaffin, 2002;Hammond & Roe, 1972;Ottaviano, Lanni, & Ceccarelli, 2001;Parkinson, Reed, & Klinkenberger, 2003;Reed, Parkinson, & Chaffin, 2003). The second one is the voxel-based method (Troy & Guerin, 2004), and the third one is the closed-form solution (Abdel-Malek, Yang, Brand, & Tanbour, 2001;Lenarcic & Umek, 1994;Sharma et al, 2004;Yang, 2003;Yang, Abdel-Malek, & Nebel 2005a, 2005b.…”
mentioning
confidence: 99%
“…The first one is the data-driven method (Hammond and Roe, 1972;Badler, 1997;Chaffin, 2002;Reed et al, 2003;Parkinson et al, 2003). It needs to collect thousands of subjects to do the experiment and visualize the collected data in the form of isosurfaces.…”
Section: Literature Reviewmentioning
confidence: 98%